Euterpe oleraceae (Açaí), Bixa orellana (Annatto), and Myrciaria dubia (Camu-camu): A Review of Preclinical Evidence of Anti-senescence Potential - de Melo, Ester Lopes; Pereira, Arlindo César Matias; Nascimento, Aline Lopes do; Carvalho, José Carlos Tavares (Pharmacognosy Reviews)
Aging is a complex process resulting from internal and external changes, culminating in a decreased efficacy of cognitive and other biological functions. Studies report that oxidative stress, immunosenescence, inflammaging, and cell senescence are involved in aging. Continuous research is performed seeking treatments delaying such processes to achieve healthy aging, including nutrition and nutraceuticals. In this article, we review the potential of some plants from the Amazon rainforest that have been gaining attention in healthspan, namely Euterpe oleraceae (Açaí), Myrciaria dubia (Camu-camu), and Bixa orellana (Annatto).
Keywords: Aging; Cell senescence; Euterpe oleracea; Myciaria dubia; Bixa orellana